DETERMINAN KEGAGALAN ASI EKSKLUSIF PADA KOMUNITAS MADURA - Otik Widyastutik; Elly Trisnawati (Fakultas Kesehatan Masyarakat, Universitas Jember, 2018)
Exclusive breastfeeding is the first intake that is very important for infants aged 0-6 months. Exclusive breastfeeding achievement in the Madurese community in the working area of ​​the outpatient Puskesmas Purun Kecil is 29%. This is due to several things including the habit of giving honey to babies, therefore in giving ASI exclusively is interrupted. This study aims to analyze the relationship between the habit of giving honey to infants aged 0-6, the support of biological mothers from the baby's mother, the support of mother-in-law from the mother's baby, the support of health officers, the working status of a mother, the knowledge of lactation management, the effort to use the independent exclusive breastfeeding, and the exclusive breastfeeding failure. This study uses a cross sectional design. The study sample was 162. The statistical test used was the Chi-square test (X2). The results showed that the determinants of exclusive breastfeeding failure in infants in Peniraman Village and Nusapati Village were the support of biological mothers from the baby's mother, mother-in-law's support of the baby's mother, health worker support, lactation management knowledge, efforts to use independent ASI dairy equipment.